Efek Mediasi Kesadaran Merek pada Pengaruh Tanggung Jawab Sosial Perusahaan Terhadap Minat Nasabah Menggunakan Produk Bank Central Asia (BCA) di Jakarta - Anthaony Ryann Welington (Universitas Tarumanagara, 2019)
This research aims to determine the role of brand awareness in mediating the effect between corporate social responsibility (CSR) towards purchase intention. The method used is a quantitative method with the type of research is descriptive. In this research, there are 3 variables : brand awareness, corporate social responsibility, and purchase intention. Sampling method used is purposive non-probability sampling with 129 respondents. The analysis technique used is mediation analysis. This research found that brand awareness as mediating variable significantly affect the relationship between corporate social responsibility (CSR) and purchase intention. Corporate social responsibility (CSR) through brand awareness have positive and significant influence simultaneously towards buying intention by 44.6%, and the rest 55.4% is influenced by other variables not examined in this research.